Bilateral orbital abscesses with subdural empyema and cavernous sinus thrombosis due to melioidosis in a child - Jayaraman, Kogilavaani; Ismail, Shatriah; Kandasamy, Regunath; Abd Karim, Ahmad Helmy (Elsevier, 2014)
Orbital cellulitis is an emergency situation in children. Rapid diagnosis and appropriate management are mandatory to save both vision and life. In contrast, melioidosis infection causing orbital cellulitis with intracranial infection is a rare situation in children, and requires an aggressive management. Poor response or worsening of clinical condition despite appropriate management of paediatric orbital cellulitis should alert the physician of this devastating infection, especially when it occurs in those living in endemic areas.